Reviews and perspectives of high impact atmospheric processes in the Mediterranean - Michaelides, Silas; Karacostas, Theodore; Sánchez, J. L.; Retalis, Adrianos; Pytharoulis, Ioannis; Homar, Víctor; Romero, Romualdo; Zanis, Prodromos; Giannakopoulos, Christos; Bühl, Johannes; Ansmann, Albert; Merinod, Andrés; et al. (My University, 2018)
The Mediterranean region is a unique area characterized by a large spectrum of atmospheric phenomena, some of which have a high impact on many aspects of human activities, safety and wellbeing. The area is long considered as a hot spot of such atmospheric phenomena deserving multidisciplinary scientific attention. The scientific research that has been carried out on these high impact atmospheric processes that occur in the Mediterranean area is indeed widespread and the available international literature is very extensive. The paper touches initially the temperature and precipitation regimes, followed by a discussion of floods and droughts. The exciting cyclogenetic patterns of explosive cyclones and medicanes are presented in separate sections. The lightning activity and the presence of dust and other pollutants are also presented herein. The atmospheric chemistry of the region which is increasingly becoming of utmost importance for the area under study is distinctly discussed. Attempts to modify the weather (the precipitation, in particular) are outlined too. The effects of climatic change on various atmospheric processes are considered throughout this paper, in addition to a dedicated section on temperature and precipitation.
Keywords: Mediterranean; Atmospheric processes; Medicanes; Explosive cyclones; Climate change; Drought; Flood; Atmospheric chemistry; Dust and pollution; Extreme weather phenomena; Weather modification